Pengaruh Inflasi, Ekspor, Impor dan Suku Bunga Luar Negeri Terhadap Nilai Tukar Rupiah Atas Dolar Amerika Periode Januari 2014 s.d.Desember 2018 - Pranoto, Hadi; Nuryadin, Rusmin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Unstable Fluctuation in the rupiah exchange rate against the US dollar can be affectedby domestic and global economic conditions. The condition of these macroeconomic factorscan make the exchange rate depreciate or appreciate.The model in this study uses a Vector Auto Regression-Vector Error Correction Mode(VAR-VECM) to see the effect of short and long term and the surprise of each variable on theresponse period January 2014 to December 2018.Based on the hypothesis's result, the VAR-VECM model shows in the long run thatexports have significance and foreign interest rates have a significant and negative effect onthe rupiah exchange rate against the dollar. At the same time, other inflation variables do nothave a substantial and positive impact on the rupiah exchange rate against the dollar. In theshort term, only the variable rupiah exchange rate variable against the dollar is significant toitself in the 1st, 3rd, and 5th lags, the imported variable in the 3rd lag, and the foreign interestvariable in the 5th lag. At the same time, other variables do not have a significant effect in theshort term.Based on the highest Response Impulse analysis, the rupiah exchange rate response tothe dollar shows an overall positive response and will be relatively stable at around 0,12%.The next highest answer is that inflation shows a positive response and will be relativelystable at about 0,07%. The export response was relatively stable in the range of 0,10% butshowed a negative response. Then the import response shows a negative and will berelatively stable at around 0,01%. The last reply to foreign interest rates showed a postivereaction and was relatively stable at about 0,01%.Based on the analysis Variance Decomposition, the most significant contribution to thevariable exchange rate of the rupiah against the US dollar is the variance of the rupiahexchange rate against itself, followed by the second-largest gift, namely inflation, followed bythe conflict of exports, imports, and foreign interest rates respectively.